2017
DOI: 10.1016/j.msea.2016.12.116
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness and hydrogen embrittlement susceptibility on the interface of clad steel pipes with and without a Ni-interlayer

Abstract: The objective of the present work has been to study the fracture properties of the interface between clad and base material of two 316L austenitic stainless steel-X60/X65 carbon steel hot roll bonded clad pipes; with and without a Ni-interlayer. Fracture mechanical tests were performed in air and under in situ electrochemical hydrogen charging to establish crack growth resistance curves and fracture initiation toughness for both systems. The results revealed that an electroplated Ni-interlayer reduces the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
8
1
1
Order By: Relevance
“…Fortunately, the cracks occurred in the direction following the pipe length, where the load is low, and were not regarded as representing any risk of pipeline failure. The cracking problem can be prevented using a Ni interlayer [17]. To the authors' knowledge, similar cracking problems with Inconel 625 have not been reported.…”
Section: Bimetallic Interface After Weldingmentioning
confidence: 66%
See 1 more Smart Citation
“…Fortunately, the cracks occurred in the direction following the pipe length, where the load is low, and were not regarded as representing any risk of pipeline failure. The cracking problem can be prevented using a Ni interlayer [17]. To the authors' knowledge, similar cracking problems with Inconel 625 have not been reported.…”
Section: Bimetallic Interface After Weldingmentioning
confidence: 66%
“…Measurements made on welded samples gave evidence that martensite was formed. The maximum microhardness values of 362 and 392 HV in the clad close to the interface for two different macros was reported [17]. Because of the carbon depletion of the pipeline steel measured by an electron probe microanalyzer (EPMA), the hardness level on the steel side close to the interface is low (156 HV).…”
Section: Production Of Clad Pipesmentioning
confidence: 99%
“…For example, [27] includes results of fracture toughness tests for compact tension (CT) specimens made of hot roll bonded clad pipes based on two 316-L austenitic stainless steel-X60 (base metal) / X65 (clad) carbon steel with and without an Ni-interlayer. The interlayer was in the crack path of the CT specimen.…”
Section: Of 20mentioning
confidence: 99%
“…The stainless steel clad plates combine the superior corrosion resistance, outstanding wear resistance, and high‐temperature oxidation resistance of stainless steel cladding with good weldability, formability, and low cost of carbon steel substrate . Meanwhile, a large amount of precious metal elements can be efficiently saved such as nickel (Ni) and chromium (Cr) elements, which is beneficial for replacing the whole stainless steel products and creating huge economic benefits .…”
Section: Introductionmentioning
confidence: 99%